Genetic risk for hospitalization of African American patients with severe mental illness reveals HLA loci - Lori, Adriana; Pearce, Brad D.; Katrinli, Seyma; Carter, Sierra; Gillespie, Charles F.; Bradley, Bekh; Wingo, Aliza P.; Jovanovic, Tanja; Michopoulos, Vasiliki; Duncan, Erica; Hinrichs, Rebecca C.; Smith, Alicia; et al. (Frontiers in Psychiatry, 2024)
We are grateful to Kimberly Kerley and Nicole A. Langford for their technical assistance in performing experiments, collecting behavioral data, data management, and recruiting; and Lynn M. Alma, Kristie Mercer, Guffanti Guia, and Jennifer Stevens for their help with genotyping, and their supports and suggestion during the preparation of this manuscript. We are thankful for the ENIGMA and CHARGE Working group for making the GWAS summary statistics available. We are grateful for the staff and participants from the Grady Trauma Project for their time and effort in supporting this research.